Effects of Diet and Temperature on the Life History of the Redlegged Ham Beetle (Coleoptera: Cleridae). Issue 1 (3rd November 2021) - Hasan, Md Mahbub; Aikins, Michael J; Mahroof, Rizana M; Phillips, Thomas W
Abstract: We investigated the effects of various foods and different rearing temperatures on the survival and development of the redlegged ham beetle Necrobia rufipes (De Geer) (Coleoptera: Cleridae), a serious pest of dry-cured hams. The diets tested were dried pet food, finely shredded copra, shredded cheese, dry-cured ham, ground fish meal, and mature larvae of Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae). As indicated by the growth index and k- values, N. rufipes populations grew fastest on the pet food and slowest on the copra. On the other hand, N. rufipes fed both ham and T. castaneum larvae produced significantly heavier larvae. The adult beetles lived significantly longer on cheese compared to other foods. Studies conducted to determine the developmental rates of N. rufipes fed pet food at temperatures of 22, 25, 28, and 31°C showed that the total developmental time and longevity of N. rufipes significantly varied at different temperatures tested. The shortest developmental time (93.32 d) was observed at 28°C. Oviposition rate was highest for females reared at 25°C while lowest at 22°C. Based on the development, reproduction, and thermal requirements, the most suitable temperature for N. rufipes was between 28 and 31°C. The results also revealed that larval cannibalism prevailed among adult beetles.